HUBUNGAN PEMBIAYAAN SIMPAN PINJAM PEREMPUAN DAN PENDAPATAN USAHA MIKRO PADA MASYARAKAT KECAMATAN PAMARAYAN KABUPATEN SERANG - Kusumawati, Nugrahini; Maryati , Sri (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
Community empowerment is closely related to the response to development issues, such as unemployment, poverty and inequality. Poverty reduction policies are not separated from the context of community development. PNPM Mandiri is one of the government programs in an effort to accelerate poverty reduction, where one of the activities in which is the development of microfinance managed by UPK (Unit Pengelola Kegiatan) in the field of Productive Economic Business or UEP (Usaha Ekonomi Produktif) in the Woman’s Cooperative Finance or we called SPP (Simpan Pinjam Kelompok Perempuan).This study aims to determine: 1) women’s credit financing activities (SPP) in Pamarayan sub-district. 2) the income micro-enterprises in communities in Pamarayan sub-district and 3) the relationbetween the women’s credit financing activities (SPP) towards community micro bussines income Pamarayan Serang District. The method used in this research is descriptive method with correlations. This method is used to prove the presence or absence of the influence of the issues examined in the group of women’s cooperative finance (SPP) in Pamarayan-Serang District. The population in this study is members of the SPP PNPM Mandiri Pamarayan who has a business. Total population in this study was 100 people from 10 groups, and samples taken as many as 50 members. The sampling technique used is proportional random sampling. Data collected by questionnaires, Data were analyzed using Statistical Analysis with SPSS version 20.The results showed that significant numbers tcount 5.924 higher than ttable 1,675 give the effect that the meaning is significant